Impact of Gadget Use on Infant and Toddler Motor and Cognitive Development in the Digital Era - Israini suriati israini; Reski Juliani; Yuli Setiawati; Patmahwati; Sri Rahayu Amri (Window of Health : Jurnal Kesehatan, 2026)
The development of digital technology has had a significant impact on various aspects of life, including child development, particularly for infants and toddlers. The use of gadgets such as smartphones, tablets, and televisions has become increasingly widespread, raising concerns about their effects on the motor and cognitive development of young children. This study aims to analyze the relationship between the duration of gadget use and motor and cognitive development in infants and toddlers aged 6 months to 5 years. The research method used is a descriptive, correlational, quantitative approach with purposive sampling, involving 150 parents of children who use gadgets. Data was collected through surveys and analyzed using Pearson correlation tests and simple linear regression. The results show a significant negative correlation between the duration of gadget use and motor development (-0.41) and cognitive development (-0.28). Children who used gadgets for longer periods showed delays in motor development, such as walking and crawling. However, the use of educational apps had a positive impact on cognitive development with a positive correlation (0.32). The study also found that age and gender did not have a significant effect on the relationship between gadget use and child development. This discussion suggests that parents should limit the duration of gadget use and prioritize physical and social activities for children to support optimal motor and cognitive development. Further research is needed to explore the impact of various types of applications on child development.